PENGARUH DIMENSI FRAUD DIAMOND DAN RELIGUISITAS TERHADAP PERILAKU KECURANGAN AKADEMIK MAHASISWA - Sistya Rahmawati; Dini Susilawati (Jurnal Akuntansi Trisakti, 2018)
This study aims to examine the factors that influence toward behavior of academic fraud by students accounting in the faculty of economics and business by using diamond fraud dimensions consisting of pressure, opportunity, rationalization, capabilities and level of religuisity.This study is using purposive convinience method, convience sanpling is a non-probability sampling technique where subjects are selected because of their convenient accessibility and proximity. Data used in this research is primary data by using questionnaire. The sample of this study is the accounting student of the faculty of economics and business of university in jakarta. This research uses multiple linear regression analysis at hypothesis testing. The result of this research shows that the opportunity, capability and level of religuisity have influence to the academic fraud behavior of the accounting students of the faculty of economics and business while the other variables such as pressure, rasionaliation and control variables have no influence on the behavior of academic fraud.